2005
DOI: 10.1159/000089167
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pelvic Stones Larger than 20 mm: Laparoscopic Transperitoneal Pyelolithotomy or Percutaneous Nephrolithotomy?

Abstract: Large pelvic stones are frequently managed with percutaneous nephrolithotomy (PCNL) but laparoscopic transperitoneal pyelolithotomy (LTP) can be an alternative. We compared PCNL and LTP for the treatment of pelvic stones >20 mm in diameter. Patients and Methods: Between November 1999 and November 2004, 16 consecutive patients, mean age 42, with a single pelvic stone >20 × 10 mm (group I), underwent LTP as first-line treatment or after shockwave lithotripsy failure. They were compared with a similar population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 32 publications
(19 reference statements)
1
47
0
1
Order By: Relevance
“…Meria and colleagues 21 and Goel and colleagues 22 found significantly longer mean operative times for LPL than for PNL (184 vs. 139 minutes, respectively, p = 0.02; and 142 vs. 72 minutes, respectively, p < 0.0001). A third non-randomized controlled trial by Gaur and colleagues 23 reported a mean operative time of 116 minutes for LPL, compared with 152 minutes for PNL (p value not stated).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Meria and colleagues 21 and Goel and colleagues 22 found significantly longer mean operative times for LPL than for PNL (184 vs. 139 minutes, respectively, p = 0.02; and 142 vs. 72 minutes, respectively, p < 0.0001). A third non-randomized controlled trial by Gaur and colleagues 23 reported a mean operative time of 116 minutes for LPL, compared with 152 minutes for PNL (p value not stated).…”
Section: Discussionmentioning
confidence: 94%
“…The mean operative time of LPL in our study, however, was acceptable and average in relation to many studies. 21,24,25 When compared with PNL, one outstanding advantage of LPL is that it is harmless to the parenchyma. 26 Therefore, the risk of bleeding is higher in PNL related to the access localization and dilation technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All endoscopic techniques, including laparoscopic approaches, have been described to treat patients with stones in ectopic pelvic kidneys. [8][9][10][11] While SWL enjoys the least invasive approach, it is associated with a significantly lower success rate compared with the rate for normal located kidneys. 1,5 Flexible ureteroscopy is another option, but it is also associated with more technical difficulties because of ureteral kink.…”
Section: Discussionmentioning
confidence: 99%